2009
DOI: 10.1158/1078-0432.ccr-08-2889
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Pharmacokinetic Study of Trabectedin as a 1- or 3-hour Infusion Weekly in Patients with Advanced Solid Malignancies

Abstract: Purpose: This study was designed to determine the safety, tolerability, and pharmacokinetics, and to seek preliminary evidence of anticancer activity of trabectedin, a novel marine-derived DNA minor grove binder, when administered as a 1-hour or 3-hour i.v. infusion for 3 consecutive weeks every 4 weeks in patients with advanced solid malignancies. The study also sought to determine the maximum tolerated dose (MTD) levels of trabectedin on these schedules, as well as to recommend doses for disease-directed stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…PK studies of both paclitaxel and trabectedin revealed high clearance rates, long half-lives, and large volumes of distribution, and PK parameters were within the range of those reported in prior single-agent studies (14,36,37). Both paclitaxel and trabectedin are substrates of cytochrome P450 metabolism (CYP3A4 and CYP2C8 for paclitaxel; CYP3A4 for trabectedin) that may be induced or inhibited by other drugs.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…PK studies of both paclitaxel and trabectedin revealed high clearance rates, long half-lives, and large volumes of distribution, and PK parameters were within the range of those reported in prior single-agent studies (14,36,37). Both paclitaxel and trabectedin are substrates of cytochrome P450 metabolism (CYP3A4 and CYP2C8 for paclitaxel; CYP3A4 for trabectedin) that may be induced or inhibited by other drugs.…”
Section: Discussionsupporting
confidence: 64%
“…Effects on WBC and neutrophils were generally reversible and rarely resulted in treatment delay. At the MTD level, grade 3 to 4 neutropenia was generally noted on day 14 (range, [7][8][9][10][11][12][13][14][15][16][17][18][19] and usually resolved to grade ≤2 on day 21 (range, 9-26). One patient each had grade 4 anemia and leukopenia, whereas four patients developed grade 4 neutropenia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations